Підготовка та організація діяльності головних суб’єктів управління школою в Нідерландах - Бойченко, Катерина (Studies in Comparative Education, 2014)
В статті розглянуто вимоги та проблеми професійної підготовки керівників шкіл у Нідерландах, а також організацію їхньої діяльності з метою виявлення позитивних рис та використання голландського досвіду в українських школах. Встановлено, що немає офіційних документів, в яких зазначаються вимоги для призначення на посаду директора школи. Педагогічна освіта не є обов’язковою для директора, який не проводить уроків у школі. Вимоги до особистості майбутнього керівника, рішення стосовно призначення на посаду, враховуючи резюме претендента, формує шкільна рада, яка має широкий рівень автономії та свободи в освіті завдяки процесам децентралізації в освітньому менеджменті. В статті зазначено, що важливими є компетентності директора-лідера, що формуються за виконання різних ролей та за різних обставин і умов. Виявлено три шляхи професійної підготовки директорів школи в Нідерландах. В статье рассмотрены требования и проблемы профессиональной подготовки руководителей школ в Нидерландах, а также организацию их деятельности с целью выявления положительных черт и использования голландского опыта в украинских школах. Установлено, что нет официальных документов, в которых указываются требования для назначения на должность директора школы. Педагогическое образование не является обязательным для директора, который не проводит уроков в школе. Требования к личности будущего руководителя, решение о назначении на должность, учитывая резюме соискателя, формирует школьный совет, который имеет широкий уровень автономии и свободы в образовании благодаря процессам децентрализации в образовательном менеджменте. В статье указано, что важные компетентности директора-лидера, формируются за выполнение различных ролей и при разных обстоятельствах и условиях. Выявлено три пути профессиональной подготовки директоров школы в Нидерландах. The article deals with the requirements for school heads professional training in the Netherlands and the organization of their work in order to define positive aspects and possibilities to use Dutch experience in Ukrainian schools. It is outlined that there are no official documents and requirements for becoming a school leader. The pedagogical education is not obligatory for the directors who don’t teach lessons. School board who decides on such matters as appointing and dismissal of the directors takes into consideration the applicants’ resume. Therefore, the future director requirements are established by the local school board which is due to high level of autonomy and freedom in education, decentralization processes in educational management. The article suggests that the competencies of the applicant are of high importance. The structure of the competencies is developed from competence roles (interpersonal, pedagogical, organizational and expert) and contexts (interaction with students, interaction with colleagues, interaction with community and self-development) and looks like as follows: interpersonal collaboration, pedagogical collaboration, organizational collaboration, collaboration with colleagues, collaboration with community, subject knowledge, reflexion and self-development. The article defines 3 ways of school directors professional training: 1) courses (MO); 2) school teachers updated professional training programme (niewe lerarenopleiding, NLO); 3) professional training university certificate (didactische aantekening). It is mentioned about the role of the State Educational Management Association (VVO), which offers short-term school directors professional training courses. The Association developes recommendations for Dutch school leaders’ professional training improvement. The complexity of school leaders functions diminishes owing to constant interaction, collaboration and agreement between educational management players and team leaders which allows to distribute effectively their duties and responsibilities. The experience of Dutch team leaders distribution and power delegation can be useful for Ukrainian school administration.